THE COMMUNICATIVE–FUNCTIONALDIMENSIONS OF RHETORICAL APPEALS INDISCOURSE - Seytzhanov Jetkerbay Elubaevich (Western European Studies, 2025)
This article examines how rhetorical appeals – often referred to by their classical labels ethos, pathos, and logos – function within discourse to achieve specific communicative goals. By synthesizing both Western and Central Asian perspectives, including contributions from Uzbek scholars such as Karimov (2018) and Tashmukhamedova (2020), it maps out the roles these appeals play in shaping speaker–hearer dynamics, establishing credibility, evoking emotional resonance, and structuring logical argumentation. Special attention is given to how cultural norms in Karakalpak and broader Uzbek communicative contexts influence the deployment and reception of these appeals. Drawing on a range of discourse-analytic studies (e.g., Fairclough, 1995; Karimov, 2018; Tashmukhamedova, 2020), this narrative explores the interplay between form and function, arguing that rhetorical strategies are deeply intertwined with the socio-pragmatic environment in which they occur. The findings aim to enrich our understanding of how speakers strategically leverage rhetorical appeals to achieve persuasive and interactive effects in varied discursive settings
Keywords: rhetorical appeals; communicative function; discourse analysis